Penetrating eye injuries in pediatric population: An epidemiological study and visual outcome - Bajracharya, Kabindra; Rai, Salma KC; Bhari, Arjun Malla; Thapa, Hari Bahadur; Hirachan, Anjita; Pandey, Saraswati; Borroni, Davide (Asian Journal of Medical Sciences, 2016)
Introduction: Penetrating eye injury is an important cause of visual impairment in pediatric population.Aims and Objectives: To study the epidemiology and visual outcome of penetrating eye injuries in pediatric population presented to Lumbini Eye Institute, the tertiary eye hospital of western Nepal.Materials and Methods: This retrospective study was conducted at the Department of Pediatric Ophthalmology and Strabismus, Lumbini Eye Institute over a period of one year from June 2014 to May 2015. All patients of penetrating eye injuries up to the age of 15 years were included in the study. The demographics of the patient, cause and duration of injury were recorded. The presenting and final best corrected visual acuity, anterior and posterior segment findings were recorded in specially designed proforma.Results: A total number of 127 children (127 eyes) presented with penetrating eye injuries during a year. The incidence of penetrating eye injury in one year was 127 out of 12927 new patients. Minimum age was 11 months, while the maximum age was 15 years with mean of 7.29 years (SD= ±3.49). Male and female patients were 99 (78%) and 28 (22%) respectively. Involvement of right eye was seen in 69 cases (54.33%) and left eye 58 (45.67%). The most common cause of injury was wooden stick in 55 cases (43.31%) followed by iron wire 12 (9.45%) and the stone 11 (8.66%). Corneal laceration was found in 102 cases (80.31%), scleral laceration in 10 (7.87%) and corneo-scleral laceration in 15 (11.81%). Seventy three percent patients were blind at the time of presentation whereas at discharge 37.63% were blind and 11.43% of patients had visual acuity better than 6/18 at presentation whereas 35.48% had visual acuity better than 6/18 after treatment.Conclusion: Penetrating eye injury is one of the common causes attending Pediatric Ophthalmology Department. Penetrating eye injury is common in male and majority of trauma is caused by wooden stick. The awareness of ocular trauma and its consequences should be increased to reduce incidence of childhood blindness.Asian Journal of Medical Sciences Vol.7(4) 2016 84-87